Fiscal Decentralization on Economic Growth (A Systematic Literature Review) - Hendana, Deni; Indrayani, Lioni; Anggraini, Anggun; Daniyal, Dasrul; Amelia, Rizka Wahyuni (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This study aims to explore the impact of fiscal decentralization on economic growth in Indonesia using the Systematic Literature Review (SLR) approach. The SLR method is used to identify, assess, and analyze findings from relevant studies on the impact of fiscal decentralization on economic growth. The SLR process includes selecting relevant scientific articles, screening, and thematic analysis to identify common patterns and significant findings. The results of the study indicate that fiscal decentralization can have a positive impact on regional economic growth, especially if supported by quality regional financial management, adequate institutional capacity, and appropriate allocation of funds to productive sectors such as education, health, and infrastructure. The results of the study indicate that regions that have weaknesses in fund management and monitoring capacity have difficulty utilizing the potential of fiscal decentralization, so that its impact on the economy is not significant. Based on these findings, this study recommends that fiscal decentralization policies focus on strengthening institutional capacity and regional financial management to maximize the potential for economic growth. Keywords:​ Fiscal decentralization, capital, economic growth, Systematic Literature Review (SLR)